2018
DOI: 10.3389/fimmu.2018.02573
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adipocytes Alters Hematopoiesis in Lipodystrophic Mice

Abstract: Adult hematopoiesis takes place in the perivascular zone of the bone cavity, where endothelial cells, mesenchymal stromal/stem cells and their derivatives such as osteoblasts are key components of bone marrow (BM) niches. Defining the contribution of BM adipocytes to the hematopoietic stem cell niche remains controversial. While an excess of medullar adiposity is generally considered deleterious for hematopoiesis, an active role for adipocytes in shaping the niche has also been proposed. We thus investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
3
18
0
1
Order By: Relevance
“…Mg 2+ deficiency is also a condition that leads to oxidative stress, increasing H 2 O 2 and lipid peroxidation [ 85 , 86 , 87 ]; therefore, Mg 2+ deficiency could affect the osteoblast/adipocyte balance not only by increasing adipogenesis due to alterations in bone homeostasis, but also by raising oxidative stress, elevating inducible nitric oxide synthase (iNOS) and H 2 O 2 [ 84 , 88 , 89 ]. Our group and others also observed previously that nutritional aspects are extremely relevant for the osteoblast/adipocyte balance [ 90 , 91 ]. It is worth mentioning that, although some studies showed that bone marrow adipocytes may have a relevant role in hematopoiesis [ 91 , 92 ], an increase in these cells in bone marrow is seen as a negative hematopoiesis regulator [ 72 ] and is related to several diseases [ 81 , 93 , 94 ].…”
Section: The Role Of Mg 2+ In Hematopoiesissupporting
confidence: 63%
See 1 more Smart Citation
“…Mg 2+ deficiency is also a condition that leads to oxidative stress, increasing H 2 O 2 and lipid peroxidation [ 85 , 86 , 87 ]; therefore, Mg 2+ deficiency could affect the osteoblast/adipocyte balance not only by increasing adipogenesis due to alterations in bone homeostasis, but also by raising oxidative stress, elevating inducible nitric oxide synthase (iNOS) and H 2 O 2 [ 84 , 88 , 89 ]. Our group and others also observed previously that nutritional aspects are extremely relevant for the osteoblast/adipocyte balance [ 90 , 91 ]. It is worth mentioning that, although some studies showed that bone marrow adipocytes may have a relevant role in hematopoiesis [ 91 , 92 ], an increase in these cells in bone marrow is seen as a negative hematopoiesis regulator [ 72 ] and is related to several diseases [ 81 , 93 , 94 ].…”
Section: The Role Of Mg 2+ In Hematopoiesissupporting
confidence: 63%
“…Our group and others also observed previously that nutritional aspects are extremely relevant for the osteoblast/adipocyte balance [ 90 , 91 ]. It is worth mentioning that, although some studies showed that bone marrow adipocytes may have a relevant role in hematopoiesis [ 91 , 92 ], an increase in these cells in bone marrow is seen as a negative hematopoiesis regulator [ 72 ] and is related to several diseases [ 81 , 93 , 94 ].…”
Section: The Role Of Mg 2+ In Hematopoiesissupporting
confidence: 63%
“…Fig. 2 and [27]), whereas heart and muscle masses were unchanged and reduced, respectively (Suppl. Fig.…”
Section: Generalized Lipodystrophy and Organomegalia In Pparg δ/δ Micementioning
confidence: 93%
“…This interesting finding was substantiated in a co-culture study of HSCs with primary human MSCs or MSC-derived adipocytes from the femoral head of patients undergoing hip surgery [58]. Whereas HSCs were stably maintained during long-term ex vivo culture with MSCs, adipocytes first induced a decline but later again an increase in colony-forming units suggesting that BM-derived adipocytes may enhance long-term maintenance of HSCs [58].…”
Section: Mat In Normal Hematopoiesismentioning
confidence: 89%